2014 Food policy timeline: Issues, actions, and events - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
The year 2014 saw mixed results for food and nutrition security: some countries made headway on policies to cut hunger, while in other countries conflict and health crises took a heavy human toll. Much of the year’s discourse focused on potential priorities for the future global development agenda.